DETERMINATION OF PREDICTION EQUATIONS TO ESTIMATE BODY CONDITION SCORE FROM BODY SIZE AND TESTICULAR TRAITS OF YANKASA RAMS - Yakubu, A.; Fakuade, O.F.; Faith, E.A.; Musa-Azara, I.S.; Agunwole, O.A. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
The study was aimed to develop prediction models using stepwise multiple linear regressionanalysis for estimating the body condition score (BCS) from the body weight (BW), testicular length(TL), testicular diameter (TD) and scrotal circumference (SC) of indigenous Yankasa rams. Data wereobtained from 120 randomly selected rams with approximately two and half years of age, from differentextensively managed herds in Nasarawa State, Nigeria. Although pairwise phenotypic correlationsindicated strong association (P<0.01) among the measured variables, there was collinearity problembetween BW and SC as revealed by the variance inflation factors (VIF) and tolerance valves (T). TheVIT was higher than 10 (VIF = 19.45 and 16.65 for BW and SC, respectively). The Twas smaller than0.1 (T = 0.05 and 0.06 in BW and SC, respectively). BW was retained among the collinear variables, andwas singly accounted for 83.7% of the variation in BCS. However, a slight improvement was obtainedfrom the prediction of BCS from BW and TL [coefficient of determination (R2), adjusted R2 and rootmean squares error (RMSE) were 85.3%, 85.1% and 0.305, respectively]. The prediction of the BCS ofYankasa rams from BW and testicular measurements could therefore be a potential tool for sustainableproduction and improvement of small ruminants in Nigeria.